EFFICIENCY OF THE PHRAGMITES AUSTRALIS AND TYPHA DOMINGENSIS ROOTS IN REMEDIATION OF POLYCYCLIC AROMATIC HYDROCARBONS (PAHS)FROM FRESHWATER SEDIMENTS - Alwan, S. W. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2016)
This study had been conducted to quantify the concentrations of PAHs compounds in the roots of Phragmites australis[Cav.] Trin. ex Steudel) and Typha domingensis Pers. and to assess their efficiency in remediation of these pollutants from the sediment of fresh water sediment in Hilla, Daghara and Diwaniyah River. Samples (whole plants) were collected from the selective sites, seasonally during 2011-2012. Results showed the efficiency of Phragmites australis and  Typha domingensis roots in the accumulation of HMW-PAHs, which were recorded (69.9 and 35.67 ng.g-1  dry weight DW) during winter and spring whereas these values were (21.8 and 38.7 ng.g-1 ) in shoots samples during the summer and autumn for both plants respectively. In contrast, LMW-PAHs compounds were not detected in some seasons and sites whereas they were recorded (4.22 and 22.1 ng.g-1) during autumn and spring at Diwaniyah and Hilla River in root samples of both plants respectively. High value of root concentration factor (RCF) had been recorded for HMW (11.7 and 4.46) during the summer at Diwaniyah and Daghara Rivers whereas low value was detected to LMW (0.38 and 0.94) during the summer at Diwaniyah River St.4 and St.5 for both plants respectively. Values of translocation factor were recorded (0.62 and 16.7) of LMW-PAHs for both plants respectively, during spring whereas low factors were recorded (0.03 and 0.1) during summer in both plants. Current study manifested that P. australis and T. domngnesis were effective in dissipation of PAHs from sediment by the accumulation of HMW-PAHs and dissipation of LMW-PAHs in the roots. Accordingly, these aquatic plants might be useful in evaluating biodegradation of PAHs in freshwater sediment.